Continuous‐time digital filtering analogue‐to‐digital converter. Issue 6 (1st March 2016) - Ratiu, A.; Morche, D.; Allard, B.; Lin‐Shi, X.; Verdier, J.
Abstract : Despite their alias‐free operation, continuous time ADCs can have their power consumption overwhelmed when presented out‐of‐band, high frequency, high amplitude signals. A new continuous time ADC architecture which, thanks to its embedded low‐pass filter transfer function is proposed, enables a power efficient quantisation in the presence of such signals. Moreover, the half‐digital nature of this approach simplifies the implementation of the proposed system compared to a standard filter‐first solution.